Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T15:22:08+01:00
A) A=(-2;3) B(4;2)
y=ax+b
3=a*(-2)+b
2=a*4+b

3=-2a+b /*2
2=4a+b

6=-4a+2b
2=4a+b

8=3b /:3
b=8/3

2=4a+b
b=8/3

2=4a+8/3
b=8/3

-4a=8/3-2
b=8/3

-4a=2/3 /:(-4)
b=8/3

a=2/3*(-1/4)
b=8/3

a=-1/6
b=8/3

y=-1/6x+8/3
a=-1/6

b ) A(-3;4) B(-1;7)
y=ax+b
4=a*(-3)+b
7=a*(-1)+b

4=-3a+b
7=-a+b /*3

4=-3a+b
21=-3a+3b

25=4b /:4
6,25=b

4=-3a+b
b=6,25

4=-3a+6,25
b=6,25

3a=6,25-4
b=6,25

3a=2,25 /:3
b=6,25

a=0,75
b=6,25

y=0,75x+6,25
a=0,75




2 4 2